THE EFFECT OF GOOD CORPORATE GOVERNANCE AND AUDIT QUALITY TOWARD QUALITY OF FINANCIAL STATEMENTS (Emprical Study In Mining Companies In Indonesia) - Riva, Isma Dwi; Maghfiroh, Siti; Primasari, Dona (Soedirman Accounting, Auditing and Public Sector Journal, 2023)
This study aims to analyze the effect of good corporate governance and audit quality toward the quality of financial statements using research method quantitative analysis. The population in this study are the mining companys that listed on Indonesia Stock Exchange. The sample of this study are financial statements from 2018-2020 within 66 company that listed on Indonesia Stock Exchange. The data use in this study were secondary data, for the sampel uses a purposive sampling method. The hypothesis testing use SPSS Version 23 for Windows. The result of this study indicates: (1) Good Corporate Governance has a positive effecct toward quality of financial statements; (2) audit quality has a negative effect toward quality of financial statements.